Synthesis , Identification and Evaluation Antimicrobial activity of some novel N-substituted Azetidinone, Imidazolidinone and Tetrazole incorporating 2- phenyl- 3- (ethyl acetate)-quinazolin-4(3H)-one - Maryam M. Sahib (Journal of Global Pharma Technology, 2018)
A novel series of azetidinone, imidazolidinone and tetrazole incorporating quinazolin-4(3H)-ones were synthesized and evaluated their antimicrobial activity in this research. Anthranilic acid as a simple molecule under acylation with benzoyl chloride yielded 2-benzamidobenzoic acid [1] followed by cyclization reaction of compound [1] with acetic anhydride yielded 2-phenyl-4H-benzo[3,1]oxazin-4-one [2] that treatment with ethyl glycinate yielded 2-phenyl-3-(ethyl acetate)-quinazolin-4(3H)-one [3] as a starting compound. Compound [3] was reacted with hydrazine hydrate to gave 2-phenyl-3-acetohydrazide-quinazolin-4(3H)-one [4]. aroyl hydrazone derivatives [5-9] prepared by reacted of compound [4] with different substitution aromatic aldehydes. Then compounds [5-9] was cyclization under three pathways with chloro acetyl chloride, 2-amino acetic acid and sodium azide to gave azetidinone derivatives [10-14], imidazolidinone derivatives [15-19] and tetrazole derivatives [20-24] respectively. Moreover the chemical structure of synthesized compounds were identified via different techniques such as FTIR,1H-NMR,and13C-NMR and some of its physical properties were measured. Also we have evaluated the effect of some prepared compounds against four types of bacterial and fungal strain. The result showed significant actions for this compound as antimicrobial agents.Keywords: Quinazolin-4(3H)-one, Schiff base, Azetidine, Imidazolidine, tetrazole, Anti-microbial.